2015
DOI: 10.1038/ncomms9785
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon nanoparticles enhance reactive oxygen levels and tumour growth inhibition in photodynamic therapy

Abstract: Photodynamic therapy (PDT) kills cancer cells by converting tumour oxygen into reactive singlet oxygen (1O2) using a photosensitizer. However, pre-existing hypoxia in tumours and oxygen consumption during PDT can result in an inadequate oxygen supply, which in turn hampers photodynamic efficacy. Here to overcome this problem, we create oxygen self-enriching photodynamic therapy (Oxy-PDT) by loading a photosensitizer into perfluorocarbon nanodroplets. Because of the higher oxygen capacity and longer 1O2 lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
577
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(581 citation statements)
references
References 22 publications
3
577
0
1
Order By: Relevance
“…The dissolved oxygen (O 2 ) in surrounding microenvironment of tumor is involved to produce toxic singlet oxygen ( 1 O 2 ) and cause the irreversible damage of tumor cell/tissue afterward 5. However, some intrinsic barriers such as the hypoxia nature of solid tumor and instantaneous short lifetime of ROS cause the low production efficiency of 1 O 2 and therefore decrease the therapeutic outcome of PDT 6. It is highly expected that the rational combination of PTT and PDT could cause the synergistically therapeutic efficacy/outcome based on their both photoinduced nature for cancer therapy 7.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolved oxygen (O 2 ) in surrounding microenvironment of tumor is involved to produce toxic singlet oxygen ( 1 O 2 ) and cause the irreversible damage of tumor cell/tissue afterward 5. However, some intrinsic barriers such as the hypoxia nature of solid tumor and instantaneous short lifetime of ROS cause the low production efficiency of 1 O 2 and therefore decrease the therapeutic outcome of PDT 6. It is highly expected that the rational combination of PTT and PDT could cause the synergistically therapeutic efficacy/outcome based on their both photoinduced nature for cancer therapy 7.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) has been proven to be a potential therapeutic strategy for cancers1 via the reaction between photosensitizers and oxygen (O 2 ) under laser to generate cytotoxic reactive oxygen species (ROS) for killing cancer cells 2, 3, 4, 5, 6. Compared to traditional cancer therapy strategies, such as surgery, chemotherapy, and radiotherapy, PDT emerges as a promising treatment method with less invasiveness, fewer side effects, and higher selectivity and efficacy 2, 4, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spontaneous exchange of O 2 and carbon dioxide (CO 2 ) results insufficient O 2 delivery 15. Hyperbaric oxygen therapy, as another method to relieve cancer hypoxia, is limited by its intrinsic side effects, such as hyperoxic seizures and barotraumas 2, 3. Recently, nanomaterials have been synthesized to deliver or generate O 2 molecules, including perfluorocarbon, CaO 2 , MnO 2 , and hydrogen peroxide (H 2 O 2 ) or catalase loaded nanoparticles 2, 3, 15, 16, 17, 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al reported the oxygen self-enriching photodynamic therapy (Oxy-PDT) by loading a near-infrared photosensitizer IR780 into perfluorocarbon nanodroplets. 177 Due to the high solubility of respiratory gases in perfluorocarbon, the perfluorocarbon is a good candidate as oxygen carrier. 178, 179 The NIR photosensitizer IR780 and perfluorohexane (PFH) were employed to prepare lipid nanodroplets with PEG on the surface (Fig.…”
Section: Tumour Microenvironment Mediated Nanotherapeuticsmentioning
confidence: 99%